Learn about time - Felicia, Law (UK : World Book, Inc.)
The Time storybook describes the adventures of Poldy and his friends during one day. The story uses familiar time concepts such as 'time to get up,' and 'time for tea'.
Poldy
Keywords: Time--Fiction; Children stories